2016
DOI: 10.1175/mwr-d-14-00399.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cumulus Cloud Updrafts as Observed with 1-Min Resolution Super Rapid Scan GOES Imagery

Abstract: A study was undertaken to examine growing cumulus clouds using 1-min time resolution Super Rapid Scan Operations for Geostationary Operational Environmental Satellite-R (GOES-R) (SRSOR) imagery to diagnose in-cloud processes from cloud-top information. SRSOR data were collected using GOES-14 for events in 2012–14. Use of 1-min resolution SRSOR observations of rapidly changing scenes provides far more insights into cloud processes as compared to when present-day 5–15-min time resolution GOES data are used. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…The short pulsing variations we observed in the maximum height and in the upper density of VHF sources in the overshooting top are consistent with the oscillations in cloud top height observed by Mecikalski et al . [] and with the constantly evolving cellular structures comprising quasi‐steady updrafts noted by Doswell and Burgess [].…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…The short pulsing variations we observed in the maximum height and in the upper density of VHF sources in the overshooting top are consistent with the oscillations in cloud top height observed by Mecikalski et al . [] and with the constantly evolving cellular structures comprising quasi‐steady updrafts noted by Doswell and Burgess [].…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Even relatively small cumulus clouds typically contain multiple updrafts overlapping in time as they grow [e.g., Blyth et al, 1988;Blyth and Latham, 1997]. Furthermore, in rapid-scan satellite imagery of cloud tops, Mecikalski et al [2016] observed oscillations of cloud top temperature and height above the LNB lasting < 10 min; they also suggested that cases in which sequential oscillations of the cloud top rising above and falling below the height of glaciation over a period of a few minutes were caused by the rise and fall of successive turrets. The short pulsing variations we observed in the maximum height and in the upper density of VHF sources in the overshooting top are consistent with the oscillations in cloud top height observed by Mecikalski et al [2016] and with the constantly evolving cellular structures comprising quasisteady updrafts noted by Doswell and Burgess [1993].…”
Section: 1002/2016jd025933mentioning
confidence: 99%
“…In the present study, we refer to the phase of the cloud coldest pixel: This method has already been used in previous studies (Mecikalski et al, 2016;Schröder et al, 2009), and we can therefore observe the beginning of the cloud glaciation. Several techniques can be used to define a cloud as liquid or ice.…”
Section: Cloud Tracking Algorithmmentioning
confidence: 99%
“…Several techniques can be used to define a cloud as liquid or ice. In the present study, we refer to the phase of the cloud coldest pixel: This method has already been used in previous studies (Mecikalski et al, 2016;Schröder et al, 2009), and we can therefore observe the beginning of the cloud glaciation. We require that each tracked cloud has its coldest pixel at least 30 min in the liquid phase and ice phase to be able to observe the phase transition.…”
Section: Cloud Tracking Algorithmmentioning
confidence: 99%
See 1 more Smart Citation